PENGARUH MODEL PEMBELAJARAN AKTIF TIPE EVERY ONE IS A TEACHER HERE BERBANTU MEDIA VIDEO EDUKATIF TERHADAP KEMAMPUAN BERFIKIR KRITIS SISWA - Mahardhika, Olivia Ersa; Gunawati, Dewi; ., winarno (PKn Progresif, 2016)
This research aimed to find out whether or not there is an effect of  Every one is a teacher here type of active learning model with educative video media aids on critical  thinking ability in the 7th graders of SMP Negeri 13 of Surakarta in the school year of 2015/2016 in Basic Competency of Elaborating the importance of Freedom of Expressing Opinion independently and responsibly. This study was a product of quantitative research with experimental type using true experimental design and with posttest only controls design. The population in this research was 7th graders of SMP Negeri 13 of Surakarta, consisting of 225 students. The sampling technique used was cluster random sampling one, in which there were two sample groups: 7th G grade as experiment and 7th F grade as control groups. Meanwhile, instrument validation was conducted using validity and reliability tests. Then, techniques of collecting data used were observation sheet, documentation sheet in the form of Learning Implementation Plan (RPP), and posttest in the form of essay test. Analytical prerequisite test was conducted using normality and homogeneity tests. Technique of analyzing data used was quantitative data with T-test analysis. Considering the result of research, it could be found that there was a difference between control and experiment grades, in which critical thinking ability measured using test obtained mean score of 82.05 for experiment and 77.69 for control grades. Thereafter, based on the result of T-test at significance level of 5%, it could be found tstatistic value of 2.396 while ttable of 1.999 (interpolation), so that the result obtained was tstatistic (2.396) > ttable (1.999). From the elaboration above, it could be concluded that there was an effect of Every one is a teacher here type of active learning model with educative video media aids on critical thinking ability Basic Competency of Elaborating the importance of Freedom of Expressing Opinion independently and responsibly. It could be seen from the difference of mean value between experiment and control grades.